1991
DOI: 10.1148/radiology.181.1.1887039
|View full text |Cite
|
Sign up to set email alerts
|

Tumor vascularization: assessment with duplex sonography.

Abstract: In this prospective study, the authors examined 123 patients with benign or malignant neoplasms (breast cancer, n = 44; liver neoplasms, n = 43; and tumors affecting other organs, n = 36) to establish general criteria for evaluation of neoplastic lesions by means of duplex sonography. The frequency shifts determined by means of different Doppler frequencies (2.31 or 3.75 MHz) were converted into flow velocities. Only the highest systolic peak flow velocity obtained from a lesion was used for statistical evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
45
2
3

Year Published

1993
1993
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(58 citation statements)
references
References 0 publications
8
45
2
3
Order By: Relevance
“…One study that combined data primarily from breast and liver malignancies reported that velocities over 40 cm/sec were indicative of malig- nancy. 5 Our data refute this, as most of the malignancies in our study had relatively slow flow and, most importantly, no statistically significant difference was observed in the blood flow velocities of benign versus malignant ovarian tumors.…”
Section: Discussioncontrasting
confidence: 46%
“…One study that combined data primarily from breast and liver malignancies reported that velocities over 40 cm/sec were indicative of malig- nancy. 5 Our data refute this, as most of the malignancies in our study had relatively slow flow and, most importantly, no statistically significant difference was observed in the blood flow velocities of benign versus malignant ovarian tumors.…”
Section: Discussioncontrasting
confidence: 46%
“…It rather constitutes a sensitive imaging modality for evaluating breast lesions. The major discrepancies between reported studies would appear to be related to the ultrasound units and the scanning techniques used (Dock et al, 1991;Schild and Fendel, 1991). The vascular resistance values in the tumour supply vessels we recorded were diametrically opposed to those reported by others (Sohn et al, 1992).…”
Section: Reaqmentioning
confidence: 96%
“…The rationale for using this technique was based on the fact that Doppler allows the assessment of angiogenesis in vivo as demonstrated by Ramos et al 24 and Dock et al 25 . Angiogenesis is an essential event in malignant tumor growth in which new vessels are formed within the tumor allowing the supply of oxygen and nutrients to tumoral cells.…”
Section: Discussionmentioning
confidence: 99%